Earnings Management on Firm Value, Audit Quality, and Managerial Ownership As Moderating Variables - Suwarno, Agus Endro; Rahiliya, Fernandaningky Dewi; Kusumawati, Eny (Universitas Muhammadiyah Surakarta, 2021)
This study aims to analyze the influence of earnings management on firm value with audit quality and managerial ownership as moderating variables. The population of this study was companies included on the LQ45 index during the 2015-2019 period. The sample was determined by the purposive sampling technique, and it obtained 85 sample companies. This research employed statistical analysis by regression analysis with moderating variables. This study revealed that earnings management affected firm value. Managerial ownership could moderate the relationship between earnings management and firm value. Meanwhile, audit quality could not moderate the relationship between earnings management and firm value.